Perancangan Sistem Informasi Registrasi Pasien Berbasis Web Di Puskesmas Tumbuan Kabupaten Seluma Tahun 2022 - Ismail Arifin; Qaka Rahma Tita; Nur Elly; Deno Harmanto (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2022)
The development of information technology is currently moving very rapidly and rapidly spreading to various fields, one of which is in the health sector. Based on PERMENKES Number 31 Year (2019) concerning Information Systems, Puskesmas must implement an Information System to assist the decision-making process in implementing the management of the Puskesmas to achieve its activity targets. This causes the data collected to be inaccurate, prone to data loss, duplication of data and the reporting takes a long time. To overcome this problem, an electronic information system will be developed so that the workload of officers will be reduced and the procedure for collecting patient data will be better, it will not take time to search and record data, and reporting can be done faster and submitted to the relevant parties. The method used to create this system uses visual basic and MySQL database and uses the DFD (data flow diagram) development method. In this study produced a prototype of the puskesmas information system which includes a login menu, an officer data input menu, patient registration and a report menu. It is recommended that the Tumbuan Health Center consider the results of the SIMPUS design so that it can be implemented immediately to support registration activities.